Peran Guru BK dalam Memfasilitasi Pembentukan Karakter Siswa Berbasis Nilai-Nilai Islam - Adinda Marsheila br Lubis; Rahmatul Maisarah; Ardi Ardi; Hidayani Syam (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research shows that most students have not shown positive personal character, where them at school who do not maximize their time, they tend use it to play with friends. Character building in education aims to overcome moral crisis that currently rife. Crises such as promiscuity, juvenile delinquency, cheating, wild racing, bullying, theft, and fighting. Character building can be done based on the willingness of the heart to change in a more positive direction. Character building that includes ethics, morals, Islamic values and educational issues with indications of growing concerns in the community and school environment. So purpose of this study is provide information about the formation of student character on Islamic values with this character education can develop all the abilities of school residents in order make good and bad decisions, exemplify, maintain wholeheartedly. This research uses descriptive qualitative research. So that the counseling teachers is important in helping them improve good learning abilities and realize student goals, and participate in educating the nation's life with various counseling services to students for the formation of student character based on Islamic values. The results showed the ability of counseling.